고분자전해질막의 수화에 의한 기계적 특성의 변화 연구 - 어준우(JUNWOO EO); 정영관(YOUNGGUAN JUNG); 서영진(YOUNGJIN SEO); 이동배(DONGBAE LEE); 황철민(CHULMIN HWANG); 김승환(SEUNGHWAN KIM) (한국수소 및 신에너지학회 논문집, 2022)
In this study, as one part of the studies on the mechanical properties of the polymer electrolyte membrane, a study was conducted on the change in the mechanical properties due to hydration before and after aging of the polymer electrolyte membrane. The mechanical properties of the polymer electrolyte membrane changes due to hydration were confirmed through tensile tests of hydrated and non-hydrated Nafion 117. As results of this study, non-hydrated membrane showed higher mechanical properties than hydrated thing in the elastic region and some plastic regions. But, it was confirmed that hydrated membrane exhibited higher mechanical properties than non-hydrated thing in the large plastic region. Hydrated membrane has a lower glass transition temperature than non-hydrated thing due to the role of water as a plasticizer. In addition, the number of ion aggregates decreases, but the size increases, and the hydrated Nafion 117 is thought to have different mechanical properties from that of the non-hydrated thing due to the characteristic that the internal attraction is strengthened.